2012
DOI: 10.1007/s10236-012-0546-4
|View full text |Cite
|
Sign up to set email alerts
|

Backtracking drifting objects using surface currents from high-frequency (HF) radar technology

Abstract: In this work, the benefits of high-frequency (HF) radar ocean observation technology for backtracking drifting objects are analysed. The HF radar performance is evaluated by comparison of trajectories between drifter buoys versus numerical simulations using a Lagrangian trajectory model. High-resolution currents measured by a coastal HF radar network combined with atmospheric fields provided by numerical models are used to backtrack the trajectory of two dataset of surface-drifting buoys: group I (with drogue)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…For surface drifters such as the tags analyzed here, this percentage is lower than the typical 3% value used in the drift of oil spills (Fallah and Stark, 1976;Wu, 1983). On average, 1.8% of the wind velocity is an optimal value that agrees with those obtained by Abascal et al (2009Abascal et al ( , 2012 with surface drifting buoys. Our results also reveal the importance of errors in wind forecasts.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For surface drifters such as the tags analyzed here, this percentage is lower than the typical 3% value used in the drift of oil spills (Fallah and Stark, 1976;Wu, 1983). On average, 1.8% of the wind velocity is an optimal value that agrees with those obtained by Abascal et al (2009Abascal et al ( , 2012 with surface drifting buoys. Our results also reveal the importance of errors in wind forecasts.…”
Section: Discussionsupporting
confidence: 83%
“…In another paper, Abascal et al (2012) demonstrated that HF radar currents combined with modeled winds are of value for the backtracking of floating objects. Their results suggest that under calm wind conditions HF radar currents could be used as a unique forcing to simulate the trajectories of surface drifting buoys with a small drogue ($ 60 cm).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous researches have proved the positive contribution of HF radar current estimates for oil spill modeling (Ullman et al, 2006), trajectory analysis of floating objects (Abascal et al, 2009), back drift estimation techniques (Abascal et al, 2012), maritime Search and Rescue operations (Ullman et al, 2003;O'Donnell et al, 2005), assimilation into numerical circulation models (Oke et al, 2002;Paduan and Shulman, 2004;Gopalakrishnan and Blumberg, 2012) or the calibration and validation of operational ocean forecasting systems (Johnson et al, 2007;Hernández et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The application of lagrangian transport models linked to hydrodynamic models has a high potential to predict various environmental scenarios. At the western Iberian margin, lagrangian transport models have been applied to the Galician coast (Carracedo et al, 2006), Ria de Vigo (Huhn et al, 2012;Abascal et al, 2012), Rio Lima estuary (Vale and Dias, 2011), Ria de Aveiro lagoon (Dias et al, 2001),Óbidos lagoon (Malhadas et al, 2009) and Tagus estuary (Braunschweig et al, 2003). The operational model MOHID-PCOMS (MOdelação HIDrodinâmica Portuguese Coast Operational Modelling System) runs in full operational mode for the western Iberian coast with daily hydrodynamic and ecological results.…”
Section: S Pando Et Al: Transport Modelling Of Organo-mineral Aggrementioning
confidence: 99%